Middle-range theory for nursing for care in the context of cardiovascular risk - Nuno Damácio de Carvalho Félix; Alba Lúcia Bottura Leite de Barros; Maria Miriam Lima da Nóbrega (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to develop a middle-range nursing theory for care in the context of cardiovascular risk. Methods: a theoretical development study, through induction through research and ICNP® practice standards, carried out in six stages: concept analysis; ICNP® terminological subset structuring; theory contextualization and purpose; proposition construction; modeling; and assumption construction. Results: the Theory of Care in the Context of Cardiovascular Risk has a middle-range scope, describing care, prescribing actions to promote health and reduce cardiovascular risk. Thirteen propositions were constructed in three categories (nursing metaparadigm, central and factorial concepts), two models and 16 assumptions. Final Considerations: the theory contributes to the construction of knowledge arising from the nursing process for care in the context of cardiovascular risk, generating propositions, assumptions and modeling, which will enable theoretical testing.